Dynamic allocation of downlink and uplink resource for broadband services in fixed wireless networks. - Leung, K.K.
We propose and analyze a resource allocation algorithm, referred to as the enhanced staggered resource allocation (ESRA) method, for fixed broadband wireless networks with directional antennas at base stations and terminals. The new method is based on the staggered resource allocation (SRA) algorithm with consideration of reception quality at terminals. Terminals are categorized into multiple classes, depending on their ability to tolerate concurrent packet transmissions. The purpose of the ESRA method is to maximize concurrent transmissions up to an extent tolerable by the receiving terminals for throughput improvement, while avoiding major cochannel interference in the networks where frequency is reused very aggressively. For practical radio parameters, the ESRA method provides 98.69% coverage and yields a maximum downlink throughput of 36.10% per sector while meeting a 15 dB signal-to-interference ratio (SIR). As for the uplink, using full power control, the throughput reaches 16.7% per sector with a packet loss probability of less than 5×10-4. The high ESRA throughput translates into a very large network capacity, and the high quality of service reveals that the new method can support real-time traffic such as voice and video, as expected in future broadband multimedia services in fixed wireless networks
Keywords: ESRA method; SIR; Base stations; Broadband multimedia services; Broadband services; Cell sectorization; Cochannel interference; Concurrent packet transmissions; Coverage; Directional antennas; Downlink resource; Dynamic resource allocation; Enhanced staggered resource allocation; Fixed broadband wireless networks; Frequency reuse; High quality of service; Maximum downlink throughput; Network capacity; Packet loss probability; Practical radio parameters; Real-time traffic; Receiving terminals; Reception quality; Resource allocation algorithm; Signal-to-interference ratio; Uplink resource; Video; Voice